2007
DOI: 10.1159/000112424
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Evoked Auditory Steady-State Responses in a Guinea Pig Model: Latency Estimates and Effects of Stimulus Parameters

Abstract: Cochlear implant speech processors typically extract envelope information of speech signals for presentation to the auditory nerve as modulated trains of electric pulses. Recent studies showed the feasibility of recording, at the scalp, the electrically evoked auditory steady-state response using amplitude-modulated electric stimuli. Sinusoidally amplitude-modulated electric stimuli were used to elicit such responses from guinea pigs in order to characterize this response. Response latencies were derived to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Electrophysiological measures from the periphery could potentially be complementary to the more central measures and can provide insight where in the auditory pathway TEM encoding is affected. Studies have shown that ECAPs can be obtained to each pulse of a modulated pulse trains both in animals 56 and humans 57 . Jeng et al 56 found that the electrically-evoked compound action potential (eCAP) modulated response amplitudes (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophysiological measures from the periphery could potentially be complementary to the more central measures and can provide insight where in the auditory pathway TEM encoding is affected. Studies have shown that ECAPs can be obtained to each pulse of a modulated pulse trains both in animals 56 and humans 57 . Jeng et al 56 found that the electrically-evoked compound action potential (eCAP) modulated response amplitudes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that ECAPs can be obtained to each pulse of a modulated pulse trains both in animals 56 and humans 57 . Jeng et al 56 found that the electrically-evoked compound action potential (eCAP) modulated response amplitudes (i.e. difference between the minimum and maximum eCAP amplitudes across a modulated cycle) show a compressive non-linear growth with increasing modulation depths, which is in line with the 40-Hz eASSR growth functions that we observed.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade several investigators have also looked at the efficacy of recording electrically evoked auditory steady state responses (EASSRs) in CI recipients. Some of these have been animal studies (Jeng et al, 2007(Jeng et al, , 2008, while others have been human studies (Ménard et al, 2004;Yang et al, 2008;Hofmann and Wouters, 2010). One consistent problem that has occurred in recording EASSRs across studies has been electrical artifact contamination produced by stimulus pulses and radio frequency (RF) transmission, especially at high stimulus intensities.…”
Section: Potential Clinical Applications Of the Assrmentioning
confidence: 99%
“…The temporal properties of neural responses, ie., the decline of the neural response following stimulus repetition (e.g., pulse trains) and the neural recovery from preceding stimuli provide information regarding neural encoding of temporal cues [11,12]. When stimuli are repeatedly presented, neural responses decrease over time.…”
Section: Introductionmentioning
confidence: 99%